TREN PENELITIAN KESEHATAN MENTAL DI ERA DIGITAL : Analisis biblimetrika pada basis data Scopus dengan menggunakan VosViewer dan Biblioshiny - Winoto, Yunus; IG, Zarra Zakiyyah (Jurnal Kesehatan Komunitas Indonesia, 2025)
The existence of social media and various digital platforms in the digital era has a major impact on human mental health. Initially, this expanded access to information about mental health and allowed us to interact with people in different places. However, excessive use of social media can increase the risk of depression and anxiety due to comparisons and competition on these platforms. To maintain well-being and good mental health in the digital age, it’s important to strike a balance in using digital tools. More in-depth studies on mental health issues in the digital age are necessary to provide insight and improve well-being. It’s also important to pay attention to research trends of this issue to stay relevant. Bibliometric analysis methods are used to explore and analyze research trends, show patterns of development, highlight dominating focuses, and understand the dynamics of knowledge growth on this topic over time. This analysis uses quantitative and statistical approaches. Based on the results, the most prolific and contributing author was Adrian Aguilera, followed by JMIR Mental Health as the most productive source. The most cited phrase is 'pandemic'. Research on mental health in the digital age is mostly conducted among women who are in adolescence. Based on the word cloud, terms that most often appear in the title are 'mental health,' 'human,' 'female,' and 'adolescent.' Recent research on this topic covers a wide range of topics, including 'female,' 'male,' to 'risk factor,' while the most common focus is humans and mental health.